2018
DOI: 10.24201/ee.v33i1.355
|View full text |Cite
|
Sign up to set email alerts
|

El efecto de la incertidumbre en la inversión extranjera directa: el caso de México

Abstract: Se investiga el efecto de la incertidumbre sobre los flujos de IED hacia el sector manufacturero mexicano durante 2007-2015. Con un panel de subsectores manufactureros estimamos un modelo por GMM en sistema, que incluye factores domésticos y externos, así como medidas de incertidumbre idiosincráticas y agregadas, como variables independientes. También se llevan a cabo simulaciones para evaluar el tamaño del efecto de la incertidumbre sobre la IED. Los resultados muestran que la incertidumbre desalienta a los f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Additionally, these results are in line with the research conducted by Noria and Fernández (2018), which states that global uncertainty has a negative and significant effect on Foreign Direct Investment in Mexico by emphasizing that uncertainty causing global shocks also reduces FDI in the manufacturing sector in Mexico (Noria and Fernández 2018), as well as the study by Lutfi et al (2022) in the context of Pakistan, which found that global uncertainty influences Foreign Direct Investment in Pakistan in both the long and short terms.…”
Section: The Association Between Wuc and Fdi Indonesiasupporting
confidence: 89%
“…Additionally, these results are in line with the research conducted by Noria and Fernández (2018), which states that global uncertainty has a negative and significant effect on Foreign Direct Investment in Mexico by emphasizing that uncertainty causing global shocks also reduces FDI in the manufacturing sector in Mexico (Noria and Fernández 2018), as well as the study by Lutfi et al (2022) in the context of Pakistan, which found that global uncertainty influences Foreign Direct Investment in Pakistan in both the long and short terms.…”
Section: The Association Between Wuc and Fdi Indonesiasupporting
confidence: 89%
“…According to the theory of irreversible investment, future political and economic uncertainty will reduce the investment of risk-neutral firms, because rational multinational investors will consider that sunk costs cannot be recovered in the event of adverse market changes [38], and the higher the degree of irreversibility of investment, the greater the re-straining influence of geopolitical risk on transnational investment [22,39]. In other words, a stable macro-political and economic environment is essential to attract foreign direct investment flows into a country and thus promote its own economic growth [40,41]. Therefore, for policy makers, countries with a high dependence on export trade will pay more attention to political peace and stability in order to encourage the introduction of foreign capital, or formulate corresponding policies to provide security for transnational investors.…”
Section: Theoretical Basis and Research Assumptionsmentioning
confidence: 99%
“…Aligned with the expectation, foreign investors tend to strategize their movement about whether they will be investing (Rodrigo & Randika, 2022). The negative effect of increasing uncertainty will be a matter for investment-determined countries because institutional quality and stable macroeconomic conditions are needed to attract FDI inflows and promote economic growth (Noria & Fernández, 2018).…”
Section: Discussionmentioning
confidence: 99%